Exploring MODIS Imagery in Monitoring Water Quality on Lake Victoria - Gidudu, Anthony; Mpakiraba, Zainab; Kalibbala, Herbert (Journal of Great Lakes Research, 2021)
At 68,800 km2, Lake Victoria is the largest fresh water lake in Africa. It is a trans-boundary water resource supporting the livelihoods of over 20 million people directly and indirectly. It is a source of food, recreation, domestic and industry use. This has rendered its monitoring of paramount interest to several environmental agencies in Uganda, Kenya and Tanzania as well as along the river Nile basin. Traditionally, the monitoring of water quality is carried out at specific points of the lake by carrying out in-situ measurements or collection of water samples for laboratory testing. This traditional approach of determining water quality is cumbersome, expensive and does not give a synoptic perspective of the whole lake. This has inspired the consideration of satellite imagery as a tool to monitor water quality on the lake. Satellite imagery offers the advantage of providing regularly collected data, giving a synoptic view of the water quality of the whole lake. The aim of this paper was to therefore investigate how satellite derived water quality parameters compare with in situ measurements in a bid to operationalise the use of satellite images in monitoring water quality on the lake. To wit, in-situ lake surface temperature at specific points was measured and water samples of those points were taken to the lab to test for Chlorophyll_a. These samples were collected within 4 hours of satellite overpass. These results were then compared with water quality parameters derived from MODIS imagery. The results showed that there is a moderate to strong correlation (R2 = 0.68) between satellite derived lake surface temperature and in-situ measurements implying that MODIS satellite imagery can be depended to accurately model the spatial variation of lake surface temperature. Unfortunately because of cloud cover coinciding with the day of in-situ observations, no similar comparisons could be made regarding Chlorophyll_a, thus portraying one of the challenges of operationalizing the use of satellite imagery in monitoring water quality on lake Victoria. Given the potential of satellite imagery as a reliable source of water quality information, further studies are urgently needed to validate it for Lake Victoria.
Keywords: MODIS; Water Quality; Lake Victoria; Validation